2019
DOI: 10.1097/pep.0000000000000550
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Perceived Self-efficacy of Physical Therapist Students Following a Pediatric Experiential Learning Opportunity

Abstract: Purpose: Physical therapists (PT) must be competent to treat patients across the lifespan, from pediatrics through geriatrics. Increasing the amount of experiential learning (EL) in pediatrics presents an opportunity for students to improve their self-efficacy in communication and patient handling. The purpose was to investigate changes in PT students' perceived self-efficacy in communication and patient handling following a structured and focused 8-week EL opportunity with a pediatric population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(64 citation statements)
references
References 11 publications
5
58
0
Order By: Relevance
“…e results of this study, in agreement with previously published research, provide favorable data to support the inclusion of EL in DPT curricula to improve students' perceptions of their clinical reasoning and self-efficacy. [4][5][6][7][8][9]21 Our findings are consistent with previous research that identified EL as an educational approach that resulted in increases in clinical reasoning of allied health students. 8,9,21 e significant difference in the change scores for the SACRR between dose groups suggests that a higher dosage of pediatric EL during the DPT curriculum could have a greater impact on students' development of clinical reasoning.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…e results of this study, in agreement with previously published research, provide favorable data to support the inclusion of EL in DPT curricula to improve students' perceptions of their clinical reasoning and self-efficacy. [4][5][6][7][8][9]21 Our findings are consistent with previous research that identified EL as an educational approach that resulted in increases in clinical reasoning of allied health students. 8,9,21 e significant difference in the change scores for the SACRR between dose groups suggests that a higher dosage of pediatric EL during the DPT curriculum could have a greater impact on students' development of clinical reasoning.…”
Section: Discussionsupporting
confidence: 89%
“…20 Collectively, the results of these studies indicate that pediatric EL, including ICE, provides students with structured learning opportunities that may lead to meaningful gains in multiple areas, including psychomotor skills, self-confidence, communication, and clinical reasoning. [4][5][6][7][8][9] Schreiber et al 1 described exemplar programs to include a mean of 11.83 6 4.4 hours of EL with child contact as a component of their pediatrics courses. Flowers et al 21 defined high-dose EL to be at least 15 hours based on the exemplar description.…”
Section: Experiential Learning In Physical Therapy Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…A commonly reported and discussed topic, therapist self-efficacy remains an important factor for skill development. Prior research has proposed mainly clinical practicum and supervision as one of the more common and effective interventions aimed at improving therapist self-efficacy [35,70,82]. These research provides strong support in our case for a communitydriven approach that aims to provide models for the novice supporters to learn from, previously outlined in section 4.2.4.…”
Section: Design Implicationmentioning
confidence: 60%